The role of nutritional support in acute pancreatitis: A review and proposal of a clinical pathway for management - Ramanujam, T.M. (Faculty of Medicine, University of Malaya, 1999)
The aim of this review is to critically analyse the available literature andto propose a rational, safe and cost-effective clinical pathway to provide nutritional support in acute pancreatitis. This pathway is proposed based on assessment of peer reviewed literature and existing generally accepted knowledge. Acute pancreatitis is a heterogeneous disease and the outcome is variable. The role of nutritional support is controversial. Acute mild pancreatitis (80%) usually does not require nutritional support unless the pre-existing nutritional is poor or complications occur. Contrary to this acute severe pancreatitis is associated with severe catabolism and a high complication rate. Nutritional depletion rapidly occurs. It is logical to support the nutrition once the patient is haemodynamically stable. Although enteral nutrition should be administered Whenever feasible, it is not always possible or advisable. Aggressive, hypercaloric parenteral nutrition administered via central venous line is not recommended. A combination of initial peripheral parenteral nutrition with fat in appropriate amount, and gradually switching over to enteral feedings is safer and cost-effective. It also avoids central line associated sepsis. The roles of newer specific therapeutic diets to enhance the immune status.